Analysis of Psychosocial Support for Workers in Tiwingan Lama Port Area Post Covid-19 Pandemic - Cindy Agnesia; Luthfi Azizah; Ajwa Salsabila Safira; Muhammad Arifin; Anggun Wulandari (Jurnal Berkala Kesehatan, 2024)
The Covid-19 outbreak significantly impacts community performance and the psychosocial well-being of workers at Tiwingan Lama port. According to Central Statistics Agency (BPS) data, the most affected businesses in the port area are food and beverage services (92.47%), general services (90.90%), and transportation and warehousing (90.34%). This research aims to provide an overview of the impact of the COVID-19 pandemic, psychological conditions, and the influence of providing psychosocial support on workers in the Tiwingan Lama port area. This study used mixed methods with a sample size of 55 people selected by purposive sampling. Quantitative data analysis technique employs Likert scale data tabulation, while qualitative data utilizes a narrative approach. The qualitative study found that during the pandemic, workers in the Tiwingan Lama port area suffered income loss which causing stress. Results showed 80% were negatively affected, while 20% were positively affected by COVID-19. However, post-pandemic, the majority of workers have good psychological conditions, which is 70%, and 30% have poor psychological conditions. This is influenced by the social support received, as evidenced by the results showing that 66% received positive social support, while the remaining 34% received negative social support.